DISCOBLOG UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI DAN PRESTASI BELAJAR EKONOMI BISNIS SISWA KELAS X AKL 2 SMK N 1 SUKOHARJO - Purnomo Sidi (Jurnal Pendidikan Ilmu Sosial, 2020)
This study aims to improve students’ collaboration skills and learning achievement of Business Economics subject through the implementation of a blog‐based Discovery Learning (DiscoBlog). The subject of this Classroom Action Research were 31 students of X AKL 2 class of SMK N 1 Sukoharjo in the even semester of the academic year 2019/2020. The data was collected using observation and tests. The observation was used to find out the students’ collaboration skills in applying DiscoBlogthrough the observation sheet. The test was used to obtain the data about students’ learning achievement of Business Economics subject through 25 multiple choice‐type questions. The data were analyzed by usingdescriptive quantitative through a mean score. The results revealed that there was an improvement in students’ collaboration skills in applying DiscoBlog. It can be seen by the increase of collaboration skills score from 63,44 in pre‐cycle to 83,33. Besides, there was an improvement in students’ learning achievement of Business Economics subject. The mean score showed a rise from 69,10 in pre‐cycle with the learning completion 54,84% to 80,97 with the learning completion 93,55%. Teachers might be able to apply these results to improve the learning quality of Business Economics subject.